2022
DOI: 10.1021/acs.jpcc.1c09193
|View full text |Cite
|
Sign up to set email alerts
|

Tale of a “Non-interacting” Additive in a Lithium-Ion Electrolyte: Effect on Ionic Speciation and Electrochemical Properties

Abstract: New lithium electrolytes compatible with high energy density cells are critical for lithium metal battery applications, but dendrite formation associated with the use of dilute organic electrolytes complicates their realization. High-concentration electrolytes mitigate some of the issues of the electrolytes but introduce additional problems, such as low conductivity and high cost. Hence, pseudo-concentrated electrolytes, wherein a co-solvent is added to a dilute electrolyte, have been presented as a possible a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Even in highconcentration electrolytes and localized high-concentration electrolytes that are currently a hot topic in electrolyte research and are expected to be commercialized, there are still reports on the use of LiPF 6 . [123][124][125][126] However, during assembly and subsequent operation of the batteries, it is still difficult to avoid acidification of the electrolyte, and using sealed batteries it is also hard to detect and suppress the occurrence of acidic failure. The acid-scavenging separators, as a functional active component, can reliably remove acidic substances and inhibit their generation within the subject LIBs.…”
Section: Discussionmentioning
confidence: 99%
“…Even in highconcentration electrolytes and localized high-concentration electrolytes that are currently a hot topic in electrolyte research and are expected to be commercialized, there are still reports on the use of LiPF 6 . [123][124][125][126] However, during assembly and subsequent operation of the batteries, it is still difficult to avoid acidification of the electrolyte, and using sealed batteries it is also hard to detect and suppress the occurrence of acidic failure. The acid-scavenging separators, as a functional active component, can reliably remove acidic substances and inhibit their generation within the subject LIBs.…”
Section: Discussionmentioning
confidence: 99%
“…The ionic conductivity of a solution is typically modeled in terms of the speciation of the electrolyte ionic components. Hence, a large number of studies have been focused on describing the ionic speciation of lithium ions in different electrolytes. At the microscopic level, computational and experimental studies have shown that the chemical structure of the anion strongly influences the ion associations; the free energy of contact-ion pair (CIP) and solvent-separated ion pair (SSIP) formation is strongly influenced by the chemical nature of the anion and the solvent; the solvation shell of the lithium ion is dictated by the structure of the solvent molecules; the solvent coordinates lithium ions with four molecules; ,, and the lithium ion solvation structure determines the nature of ion speciation. ,,, Furthermore, the macroscopic properties of the electrolyte are strongly influenced by the chemical nature of the solvent and the counteranion in the electrolyte. For example, the formation of CIPs, aggregates (i.e., clusters of CIPs), and SSIP solvation species influences not only the conductivity and viscosity but also the electrochemical window of the electrolyte. , Hence, understanding how the counteranion and the solvent influence the ion speciation is paramount to electrolyte design.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a large number of studies have been focused on describing the ionic speciation of lithium ions in different electrolytes. 20 22 At the microscopic level, computational and experimental studies have shown that the chemical structure of the anion strongly influences the ion associations; 23 25 the free energy of contact-ion pair (CIP) and solvent-separated ion pair (SSIP) formation is strongly influenced by the chemical nature of the anion and the solvent; 13 the solvation shell of the lithium ion is dictated by the structure of the solvent molecules; 26 28 the solvent coordinates lithium ions with four molecules; 26 , 27 , 29 and the lithium ion solvation structure determines the nature of ion speciation. 11 , 28 , 30 , 31 Furthermore, the macroscopic properties of the electrolyte are strongly influenced by the chemical nature of the solvent and the counteranion in the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…21 Combining this relationship with (2) Applying Walden's analysis to the LiFSI in DMC systems, in line with previous works, in Figure 1b we see clearly that the product Λη is not constant across salt concentration or with the addition of diluent. 4,16,19,20 This indicates that more complex ion and solvent interactions are responsible for the decrease in conductivity at low solvent:salt ratios (high concentrations). If we were to assume only ideal interactions and full ion dissociation, this would suggest that the effective ionic radius decreases with an increasing salt concentration.…”
mentioning
confidence: 98%
“…Similar to previous studies, we find that viscosity effects alone are insufficient to describe transport property differences across the classes of studied electrolytes. 4 , 16 , 19 , 20 Next we examine the electrophoretic mobility and transference number. Without making any assumptions about solution ideality, we demonstrate through Onsager transport theory that HCEs have high transference numbers owing to a decrease in cation–anion correlated motion and an increase in positive cation–cation correlations, consistent with a coordinated Li-ion hopping transport mechanism.…”
mentioning
confidence: 99%